2020
DOI: 10.1109/access.2020.3008551
|View full text |Cite
|
Sign up to set email alerts
|

Back-to-Back Microstrip Antenna Design for Broadband Wide-Angle RF Energy Harvesting and Dedicated Wireless Power Transfer

Abstract: A novel back-to-back microstrip antenna is proposed to cover 2G/3G/4G/5G communication bands and ISM-2.4 GHz, ISM-5.8 GHz to simultaneously realize broadband wide-angle ambient wireless energy harvesting and dedicated wireless power transfer. The ground mode radiation is introduced by the limited-sized ground, with the loading of the patches and shorting vias, to form a broadband resonance from 2 GHz to 4 GHz. Furthermore, a resonance at ISM-5.8GHz is also excited with high-directivity. On the basis of ensurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Moreover, the proposed antenna should also have a high radiation efficiency and high gain to maximize the received RF power from the ambient RF sources. In previous works, numerous planar wideband antennas have been developed to collect RF energy from several frequency bands [81][82][83][84]. However, most of them are unable to obtain the satisfactory gain.…”
Section: Rf Energy Harvestingmentioning
confidence: 99%
“…Moreover, the proposed antenna should also have a high radiation efficiency and high gain to maximize the received RF power from the ambient RF sources. In previous works, numerous planar wideband antennas have been developed to collect RF energy from several frequency bands [81][82][83][84]. However, most of them are unable to obtain the satisfactory gain.…”
Section: Rf Energy Harvestingmentioning
confidence: 99%
“…In addition, recent studies have also conducted RFEH research on cellular bands and wireless local area network (WLAN) frequencies. To efficiently implement RFEH, several antennas have been implemented for wide bandwidth [6], [7], [8], [9], [10], multiple bands [11], [12], [13], wide beamwidth [14], [15], [16], [17], and high gain [18]. For applications such as IoT sensors, studies for compactness or flexibility have also been conducted [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve wide bandwidth for the RFEH, most of the antennas consist of wide radiators [6], [7], [8], [9], [10], making surface current distributions correspond to each frequency. Reference [9] used the elliptical slot of the radiator to improve bandwidth, and [7] showed that the slot under the feedline can improve impedance matching.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation